Legal Protection for Phishing Victims : Reviewed from Indonesian Positive Law - Olivia Audriana Putri; E. Imma Indra Dewi Windajani (Westscience Press, 2024)
In this age of digitalization, phishing has become a crime that is close to human life. In phishing crimes, the perpetrator's identity is mostly unknown or anonymous. The perpetrator's identity is the primary key for processing a lawsuit in court. Victims who don’t know the real identity of the phisher will not be able to file a lawsuit for compensation. This study aims to determine the legal protection the state provides to phishing victims, especially in terms of compensation. This research uses a juridical-normative method with data collection through a literature study. Law No. 1 of 2024 on the Second Amendment to Law No. 11 of 2008 regarding Electronic Information and Transactions (ITE Law), Law No. 27 of 2022 regarding Personal Data Protection (PDP Law), and other constitutional regulations are the primary legal materials in this research. The secondary legal materials are relevant research results, journals, and books. Based on the research conducted, it has been shown that it’s necessary to establish the real identity of the perpetrator who can be responsible for compensating the victims of phishing. The difficulty of finding phishers who can hide their real identities and digital footprints are the main obstacle to compensating phishing victims.